Natural Killer Cells for Immunotherapy – Advantages of the NK-92 Cell Line over Blood NK Cells - Klingemann, Hans; Boissel, Laurent; Toneguzzo, Frances (Frontiers in Immunology, 2016)
Natural killer (NK) cells are potent cytotoxic effector cells for cancer therapy and potentially for severe viral infections. However, there are technical challenges to obtain sufficient numbers of functionally active NK cells from a patient’s blood since they represent only 10% of the lymphocytes and are often dysfunctional. The alternative is to obtain cells from a healthy donor, which requires depletion of the allogeneic T cells to prevent graft-versus-host reactions. Cytotoxic cell lines have been established from patients with clonal NK-cell lymphoma. Those cells can be expanded in culture in the presence of IL-2. Except for the NK-92 cell line, though, none of the other six known NK cell lines has consistently and reproducibly shown high antitumor cytotoxicity. Only NK-92 cells can easily be genetically manipulated to recognize specific tumor antigens or to augment monoclonal antibody activity through antibody-dependent cellular cytotoxicity. NK-92 is also the only cell line product that has been infused into patients with advanced cancer with clinical benefit and minimal side effects.